Aplicación de la NIC 16 en la Empresa Conzaelect S. A, de la ciudad de Guayaquil, periodo 2023. - Reyes Ochoa, Fernanda Catalina (2024)
This case study was developed in the company Conzaelect S.A, in the city of Guayaquil, with the objective of evaluating compliance with IAS 16 in the company Conzaelect S.A during the period 2023, through a review of the Statement of Financial Situation in accordance with what the regulations establish. The applied methodology was based on a mixed cross-sectional approach, descriptive, documentary and field research types, as well as direct observation techniques and interviews with their respective investigative instruments. The results were: the organization's accountant has basic knowledge about the technical recommendations in the accounting treatment of the “Property, plant and equipment” account, recognizes the importance of recognizing the useful life of the asset, its initial costs and depreciation for its registration in the accounting books, also the relevance of executing an adequate accounting treatment of fixed assets, because it facilitates an optimal decision process; The company does not present the accumulated depreciation of fixed assets in the accounting book, a negative aspect that denotes inefficient management of accounting information and non-compliance with IAS 16. In conclusion,